# Untitled unknown
plain_text
a month ago
1.7 kB
2
Indexable
Never
```For a random variable X and a constant a, show that \$Var(aX) = a^2V ar(X)\$

Knowing that \$\$ Var(X) = E[(X-E(X))^2] = E(X^2)-[E(X)]^2\$\$

Then:

\$\$
Var(aX) = E[(aX)^2] - [E(aX)]^2
\$\$

\$\$
Var(aX) = E[a^2X^2] - [aE(X)]^2
\$\$

\$\$
Var(aX) = a^2E[X^2] - a^2[E(X)]^2
\$\$

\$\$
Var(aX) = a^2[E(X^2) - E(X)^2]
\$\$

\$\$
Var(aX) = a^2Var(X)
\$\$

2.  For random variables X and Y,show that \$Var(X+Y)=Var(X)+Var(Y)+2Cov(X,Y)\$.

Knowing also that

\$\$
Cov(X, Y) = E[(X-E(X))(Y-E(Y))] = E(X,Y) - E(X)E(Y)
\$\$

Then:

\$\$
Var(X + Y) = E[(X + Y-E(X+Y))^2]
\$\$

\$\$
Var(X+Y) = E[(X +Y - E(X) -E(Y))^2]
\$\$

\$\$
Var(X + Y) = E[[(X-E(X)) + (Y-E(Y))]^2]
\$\$

\$\$
Var(X + Y) = E[(X - E(X))^2 + (Y-E(Y))^2+2(X-E(X))(Y-E(Y))]
\$\$

\$\$
Var(X + Y) = E[(X - E(X))^2] + E[(Y-E(Y))^2]+2E[(X-E(X))(Y-E(Y))]
\$\$

\$\$
Var(X + Y) = Var(X) + Var(Y) +2Cov(X,Y)
\$\$

3.  For random variables X and Y , show that \$Cov(X, Y ) = E(XY ) − E(X)E(Y )\$.

\$\$
Cov(X,Y)=E[(X-E(X))(Y-E(Y))]
\$\$

\$\$
Cov(X,Y)=E[XY-XE(Y)-YE(X)+E(X)E(Y)]
\$\$

\$\$
Cov(X,Y)=E[XY]-E[XE(Y)]-E[YE(X)]+E(X)E(Y)
\$\$

\$\$
Cov(X,Y)=E[XY]-E(X)E(Y)-E(Y)E(X)+E(X)E(Y)
\$\$

\$\$
Cov(X, Y ) = E(XY ) − E(X)E(Y)
\$\$

4.  For random variables X and Y and constants a and b, show that \$Cov(ax, bY ) = abCov(X, Y )\$.

\$\$
Cov(aX, bY ) = E[(aX)(bY)]-E(aX)E(bY)
\$\$

\$\$
Cov(aX, bY ) = E[(abXY)]-E(aX)E(bY)
\$\$

\$\$
Cov(aX, bY ) = abE[XY]-[aE(X)[bE(Y)]
\$\$

\$\$
Cov(aX, bY ) = ab[E(XY)-E(X)E(Y)]
\$\$

\$\$
Cov(aX,bY) = abCov(X,Y)
\$\$```